Penggunaan Bahasa Pemrograman Maple untuk Menyelesaikan Masalah Mekanika Gerak dalam Fisika - Fajar Pratama Pongsapan; Ishak Pawarangan (Publikasi dan UKI Press UKI Toraja., 2021)
Use of Maple Programming Language to Solve Motion Mechanics Problems in Physics. In this paper, we have solved one of the classical mechanics case that is the strain and acceleration force of each connected object through the pulleys using Maple programming language. Maple is a computer-based mathematical software, that is algebraic computer system capable of solving equations in the form of numerical solutions And symbolic. Computing and visualization capabilities with ease of use and integrated operator support, functionality and mathematical solutions are the reason for this program being selected. Maple method and language are very potential in solving the some cases of physics.